PERILAKU LENTUR BALOK CASTELLATED MODIFIKASI DENGAN PENYAMBUNG PROFIL SIKU DAN KOMPOSIT MORTAR - , MUHAMMAD HAIDAR AULIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The castellated beam is the modification result of wide flange shapes with various shapes of opening in the web and it is carried out by increasing the height of the wide flange shape section which can also increase more flexural capacity more than the wide flange shape with standard size without selecting larger profile size. The higher the beam section, the slimmer the beam will be. Thus, the possibility of local buckling will be difficult to avoid. Striving to cope with such weakness, the objective of this research is to study the flexural behavior of castellated beam stiffnessed by angle shapes encased with mortar. This study aims to know about flexural behavior of castellated beam stiffnessed by angle shapes encased with mortar. The tests carried out on 1 piece beam. Installation of profile stiffener by welding methods. Mix design mortar used is weight ratio of 1:1.5